Improved Safety and Cost Savings from Reductions in Cast-Saw Burns After Simulation-Based Education for Orthopaedic Surgery Residents. (6th September 2017) - Bae, Donald S.; Lynch, Hayley; Jamieson, Katherine; Yu-Moe, C. Winnie; Roussin, Christopher
Abstract : Background: The purpose of this investigation was to characterize the clinical efficacy and cost-effectiveness of simulation training aimed at reducing cast-saw injuries. Methods: Third-year orthopaedic residents underwent simulation-based instruction on distal radial fracture reduction, casting, and cast removal using an oscillating saw. The analysis compared incidences of cast-saw injuries and associated costs before and after the implementation of the simulation curriculum. Actual and potential costs associated with cast-saw injuries included wound care, extra clinical visits, and potential total payment (indemnity and expense payments). Curriculum costs were calculated through time-derived, activity-based accounting methods. The researchers compared the costs of cast-saw injuries and the simulation curriculum to determine overall savings and return on investment. Results: In the 2.5 years prior to simulation, cast-saw injuries occurred in approximately 4.3 per 100 casts cut by orthopaedic residents. For the 2.5-year period post-simulation, the injury rate decreased significantly to approximately 0.7 per 100 casts cut (p = 0.002). The total cost to implement the casting simulation was $2, 465.31 per 6-month resident rotation. On the basis of historical data related to cast-saw burns (n = 6), total payments ranged from $2, 995 to $25, 000 per claim. The anticipated savings from averted cast-saw injuries and associated medicolegal payments in the 2.5 years post-simulation was $27, 131, representing an 11-to-1 return on investment. Conclusions: Simulation-based training for orthopaedic surgical residents was effective in reducing cast-saw injuries and had a high theoretical return on investment. These results support further investment in simulation-based training as cost-effective means of improving patient safety and clinical outcomes. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.